Sound Source Localisation in Digital Hearing Aids: A Review of Critical Factors - SCALITI, Fermín; EVIN, Diego A.; TOMMASINI, Fabián C. (Archives of Acoustics, 2025)
Sound source localisation is a fundamental ability for a listener’s functional interaction with the environment, yet it remains a significant challenge for hearing aid users. In general, they perform worse on spatial hearing tests than individuals with normal hearing. This narrative literature review examines the critical factors affecting sound source localisation when hearing aids are worn, with a focus on direction identification. We analysed peer-reviewed articles published over the past three decades to evaluate the impacts of the type of fitting, form factor, acoustic coupling, processing delay, bandwidth, directional microphones, and dynamic range compression on localisation ability. As a general conclusion, there is a consensus in the literature that binaural and open fittings, with microphones at the ear entrance and with extended bandwidth, significantly improve localisation performance. In addition, this review is intended to provide valuable information that can guide future innovations in hearing aid technology to improve users’ hearing experiences and their integration into the environment.